The Emerging Role of Central and Peripheral Immune Systems in Neurodegenerative Diseases - Zang, Xin; Chen, Si; Zhu, JunYao; Ma, Junwen; Zhai, Yongzhen (Frontiers in Aging Neuroscience, 2022)
For decades, it has been widely believed that the blood–brain barrier (BBB) provides an immune privileged environment in the central nervous system (CNS) by blocking peripheral immune cells and humoral immune factors. This view has been revised in recent years, with increasing evidence revealing that the peripheral immune system plays a critical role in regulating CNS homeostasis and disease. Neurodegenerative diseases are characterized by progressive dysfunction and the loss of neurons in the CNS. An increasing number of studies have focused on the role of the connection between the peripheral immune system and the CNS in neurodegenerative diseases. On the one hand, peripherally released cytokines can cross the BBB, cause direct neurotoxicity and contribute to the activation of microglia and astrocytes. On the other hand, peripheral immune cells can also infiltrate the brain and participate in the progression of neuroinflammatory and neurodegenerative diseases. Neurodegenerative diseases have a high morbidity and disability rate, yet there are no effective therapies to stop or reverse their progression. In recent years, neuroinflammation has received much attention as a therapeutic target for many neurodegenerative diseases. In this review, we highlight the emerging role of the peripheral and central immune systems in neurodegenerative diseases, as well as their interactions. A better understanding of the emerging role of the immune systems may improve therapeutic strategies for neurodegenerative diseases.